Fictions in the Thought of Sir John Salmond - Frame, Alex (Victoria University of Wellington Law Review, 1999)
A Lecture delivered for the Stout Centre’s "Eminent Victorians" Centennial Series in the Council Chamber, Hunter Building at Victoria University on 31 March 1999. The author pays tribute to the late Sir John Salmond by discussing the role of "fiction" in law and in the thought of Sir John. The author notes the nature of fiction as a formidable force, as it facilitates provisional escape from the tyranny of apparent fact and forget about the suspensory nature of fiction. There are three types of "fictions" in the legal world: legislative fictions, whereby the world is refashioned in accordance with the legislator’s desires; constitutional fictions, which places fictional boundaries on government rule; and corporate fiction, which creates a fictional corporate personality for companies. The author concludes that it is purpose that keeps fiction honest, and that the relationship between fiction and purpose is just as important as that between hypothesis and fact.